ICF Personal Factors Strengthen Commitment to Person-Centered Rehabilitation – A Scoping Review - Karhula, Maarit; Saukkonen, Sari; Xiong, Essi; Kinnunen, Anu; Heiskanen, Tuija; Anttila, Heidi (Frontiers in Rehabilitation Sciences, 2021)
Background: The ICF classification is a biopsychosocial frame of reference that contributes to a holistic understanding of a client’s functioning and the factors involved. Personal factors are not currently classified in the ICF due to large societal and cultural diversity and lack of clarity in the scope of such factors. Aims: To ascertain which factors in the ICF classification have been defined as personal factors in different studies and what conclusions have been drawn on their role in the ICF classification. Methods: The study was a scoping review. A systematic search for articles published in 2010–2020 was performed on the Cinahl, Pubmed, ScienceDirect and Sport Discus databases. The personal factors specified in the articles were classified according to the seven categories proposed by Geyh et al: socio-demographic factors; position in the immediate social and physical context; personal history and biography; feelings; thoughts and beliefs; motives; and general patterns of experience and behavior. Results: The search yielded 1 988 studies, of which 226 met the inclusion criteria. The studies had addressed a wide variety of personal factors that were linked to all seven categories defined by Geyh et al. Some studies had also defined personal factors that were linkable to other components of the ICF or that did not describe functioning. About 22% (51) of studies discussed the role of personal factors in rehabilitation. Conclusions: The range of personal factors in the ICF classification addressed in the reviewed studies is wide. Personal factors play an important role in rehabilitation. However, according to the reviewed studies, a more precise coding of personal factors is not yet warranted.